About the Relevance of the Economic Lexis - Lulanski, Pano (Research Papers, 2004)
The incorrect utilization of the economic terms is a sign for underdevelopment of the economic science and supposes searching for adequate, to real process, terms of the relevant phenomenon.The lack of relevance of the economic lexis is shown at first place, on the matter of forming the macro-classification of the recapitulated activities and at second place, on the matter of the incorrect utilization of some terms.There is a critical examination of the classification of the recapitulated activities: business and not business activities, economic and not economic activities, public and private activities, merchant and not merchant activities.From the point of view of the lack of relevance of the usual terms, there is analysis of the defects of the expressions: commodities and services, market economy and market business, economy and business.